To be or not to be reunited : when family reunification in not in the best interest of the unaccompanied minor - Branco, Márcia Maria Mendes de Mansilha (2024)
This dissertation aims to examine the right to family reunification for unaccompanied minors in the European Union and its intimate connection to the principle of the best interests of the child. Although this principle is widely reflected in international and European regulations, its application in cases of assessment of requests for family reunification requires a careful case-by-case assessment. The aim of this study is to highlight the inherent vulnerability that accompanies unaccompanied minors in particular, the benefits associated with swift and efficient family reunification, and the possibility that reunification applications may be wrongly assessed, with far-reaching legal, psychological and social consequences.